If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x+1=-1x-3
We move all terms to the left:
3x+1-(-1x-3)=0
We get rid of parentheses
3x+1x+3+1=0
We add all the numbers together, and all the variables
4x+4=0
We move all terms containing x to the left, all other terms to the right
4x=-4
x=-4/4
x=-1
| 4,3+3,2x=5,2x+7,3 | | 6+7(-x+4)=76 | | 53+100(x+14)=180 | | a÷27=9÷81 | | -7x+33=69-x | | -75=5+5(-4x+4) | | 2.5m-18=32 | | 4x+2=2x+18* | | 4-4(3-8x)=8x+40 | | X^2=68-y | | 5.7=-2.5x+18-1/6 | | 3+3(1-5x)=-84 | | 13x+36+118=180 | | 60+60+3x=180 | | -1x-2=-2x-8 | | 42=3xx= | | 5w-3.2=9.3 | | -3x=50=5 | | 5(2x+5)=4(2x+5)+3x | | 271-x=187 | | -u+250=49 | | 5(3x-1)-4x=17 | | 260=163-x | | 10x-15=9x-1 | | 4x-6=-x-1 | | 1x+25=2x+15 | | 2(-8+4x)+3=51 | | x^2−8x−48=0 | | 5x-3=4x-21 | | 8+4x=8x-32 | | (4y+6)+(7y+7)+(20y-11)=360 | | 3c=7-4c |